Boundary Controllability of Semilinear Impulsive Sobolev-type Neutral Integrodifferential System with Timevarying Delays in Banach Space - Radhakrishnan, B.; Chandru, P. (Discontinuity, Nonlinearity, and Complexity, 2026)
In this article, sufficient conditions for the boundary controllability of semilinear impulsive Sobolev-type neutral integrodifferential functional evolution systems with timevarying delays in Banach spaces have been established. The results are obtained by using two-parameter family of evolution operators and fixed point theorem. An example is provided to illustrate the theory.